2021
DOI: 10.1007/s00429-021-02279-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric differences in altered reactivity of brain oscillations at rest after posterior lesions

Abstract: A variety of evidence supports the dominance of the right hemisphere in perceptual and visuo-spatial processing. Although growing evidence shows a strong link between alpha oscillations and the functionality of the visual system, asymmetries in alpha oscillatory patterns still need to be investigated. Converging findings indicate that the typical alpha desynchronization occurring in the transition from the eyes-closed to the eyes-open resting state might represent an index of reactivity of the visual system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 84 publications
(138 reference statements)
0
12
0
Order By: Relevance
“…From this perspective, interconnected attentional networks [105,106], regulating attentional allocation in visual space, might participate in these defensive mechanisms, promoting effective scanning and visual analysis of the environment. Thus, the well-known dominance of the right hemisphere in visuo-spatial performance [107][108][109][110][111][112], and attentional allocation [105,106,[113][114][115], might have favored connections and reciprocal signaling between the emotional subcortical circuit and the attentional networks within the same hemisphere, therefore strengthening the right-lateralized prevalence in rapid and unconscious detection of threat.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, interconnected attentional networks [105,106], regulating attentional allocation in visual space, might participate in these defensive mechanisms, promoting effective scanning and visual analysis of the environment. Thus, the well-known dominance of the right hemisphere in visuo-spatial performance [107][108][109][110][111][112], and attentional allocation [105,106,[113][114][115], might have favored connections and reciprocal signaling between the emotional subcortical circuit and the attentional networks within the same hemisphere, therefore strengthening the right-lateralized prevalence in rapid and unconscious detection of threat.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, in light of the importance of posterior cortices in generating, distributing and coordinating oscillatory patterns (Hindriks et al 2015 ; Thut et al 2011 ; Bollimunta et al 2008 ; Romei, et al 2008a , b ), it is of great interest to study the effects of lesions to these cortices on oscillations also at the network level. Indeed, as previously mentioned, evidence on hemianopic patients has shown that lesions to posterior cortices alter oscillatory activity at rest and that these alterations might represent a biomarker of the functionality of the visual system (Pietrelli et al 2019 ; Gallina et al 2021 ). However, it is still unknown whether lesions to posterior cortices might also induce specific post-lesional alterations of functional connectivity patterns in different frequency bands during resting state.…”
Section: Introductionmentioning
confidence: 94%
“…More precisely, posterior brain lesions in hemianopic patients have been shown to selectively reduce the alpha peak and power during rest, while the same was not observed after lesions to anterior regions (Pietrelli et al 2019 ), suggesting a role of posterior cortices in generating and distributing alpha oscillatory activity at rest. Moreover, evidence has shown that lesions to posterior cortices (and not lesions to anterior cortices) alter also the typical alpha power reduction observed in the transition from the eyes-closed resting state to the opening of the eyes (i.e., alpha reactivity; Gallina, et al 2021 ). Interestingly, when alpha reactivity was more severely impaired after right posterior lesions, a concurrent disruption in reactivity in the theta range at the opening of the eyes was also observed (Gallina et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other functions such as visual imagery are dominant in the left hemisphere for orthographic images and in the right for exogenous stimuli (Liu et al 2021;this issue). Some other functions do not even have an exact name or definition, such as the right hemispheric orchestration of oscillatory patterns to support visual processing (Gallina et al 2021;this issue). Hence, a significant amount of work is still required to polish the functional fabric of the human mind as we understand it before we can assess their functional and structural lateralisation comprehensively and with satisfying accuracy.…”
mentioning
confidence: 99%